Penentuan Nasab Anak pada Pasangan Married by Accident (MBA) - Dhea Indryani (Journal Innovation In Education, 2024)
This study aims to analyze the factors underlying the occurrence of married by accident, to explain how the marriage process and the status of the lineage of children born from couples married by accident. This study uses a normative-empirical research method. The data collection techniques used are observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, drawing conclusions and checking the validity of findings with triangulation. Based on the results of the study, it shows that married by accident. The marriage process for couples married by accident is the same as other couples, but without a proposal and with special marriage guidance. The status of the lineage of children born from couples married by accident, the Constitutional Court decision which changed the contents of Article 43 paragraph (1) of Law Number 1 of 1974 concerning Marriage, allows children of adultery to be traced to their father and mother in order to achieve the goal of the issuance of Islamic law. In the view of maqashid sharia, maintaining religion, soul, mind, descendants, and property for children born out of wedlock is important to maintain, because losing one of them can damage the child.